The incidence of Thyroid Carcinoma in Multinodular Goiter: retrospective analysis - Gandolfi, P.P.; Frisina, A.; Raffa, et al., M. (Acta Biomedica Atenei Parmensis, 2004)
Thyroid carcinoma (TC) is a relatively rare tumour, but it represents the most frequent form of cancer of the endocrine glands. Epidemiologically ascertained risk factors are ionising radiation, the presence of thyroid adenoma and multinodular goiter (MNG).Multinodularity of goiter should no longer be considered an indicator of probable benign disease. A retrospective analysis was performed on patients operated of MNG at the Unit of Otolaryngology, Sanremo Hospital (Italy) from January 1st 1995 to December 31st 2002, in order to establish the incidence of carcinoma. The results of this retrospective study, demonstrate that in 13.7% of the patients operated for goiter, the presence of a carcinoma was noticed in the definitive histopathologic examination. Such incidence percentage of MNG is in accordance with the data reported in published reports. Thus, the authors conclude that the risk of malignancy in MNG has not to be underestimated, and that a dominant nodule in MNG should be valued as if it were a solitary nodule in an otherwise normal gland.